Pengaruh Senam Otak Terhadap Kecemasan pada Anak Usia Sekolah Yang Mengalami Hospitalisasi - Sarifah, Sarifah; Arbianingsih, Arbianingsih; Huriati, Huriati (Journal of Islamic Nursing, 2016)
Anxiety in hospitalization will lead to the uncomfortable feeling good in children and families, so that the necessary process of adjustment to reduce, minimizing the anxiety to not develop into a crisis. One of media treatment in lowering anxiety is brain gym . Brain gym is a series of simple gestures that simulates brain work and brain function optimally. Study aims to determine the influence of brain gym of anxiety in children of school age who have hospitalization. True Eksperimental pre test post test control group design. Research place at Islam Faisal hospital Makassar and Labuang Baji hospital Makassar. The data analysis used Independen T-test. The gathering samples using methods Random Allocation. Provided 14 samples with 7 respondents of intervention group and 7 of respondents as a control group. The result of test statistic obtained by velue = 0,000, then there was a meaningful level of anxiety pre-Test with post Test after use brain gym.  If a person to experience anxiety then the cortex cerebri to send a distress signal to hypothalamus thus resulting in tension in motoric, hyperactivity of aoutonomic nervous system and raise awareness. The method used to help in lowering anxiety by doing brain gym. With movements brain gym can activate the neocotex and nervous parasympathetic reduce increase in the hormone adrenaline in body that can ease the tension of phychological and physical strain. So, conclusion is brain gym effect on reducation of anxiety and therapy is able to be one alternative for children who have hospitalization.